(3edM GdHjGf aj JaSjQ TF ef GdbQBfs - (3CMeO Hf eMeO Hf Ydj GdMUcaj, GHf GdedG ,J (B1003 (3g` s
(3ChdgG (B:s
(3fMeOc Gddge Ydi fYeJc GdJi dG JMUi hfTcQc Ydi fYec GdJi dG JSJbUi s
(3BNQgG (B:s
(3eYfG NWhGJfG ai RjGQI bHd hVhM ef SGYI GfJgi cdeGJg ef MQha s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B235 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B133s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs